2014
DOI: 10.3389/fevo.2014.00018
|View full text |Cite
|
Sign up to set email alerts
|

Mate recognition and reproductive isolation in the sibling species Spodoptera littoralis and Spodoptera litura

Abstract: Mate recognition is crucial for reproductive isolation and for maintaining species integrity. Chemosensory-mediated sexual communication with pheromones is an essential component of mate recognition in moths. Confronted with sex pheromone stimuli released from conspecific and closely related heterospecific females, which partially overlap in chemical composition, male moths are under strong selection to recognize compatible mates. Here, we investigated the role of pheromone signals in premating communication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 42 publications
0
55
0
Order By: Relevance
“…It is a serious pest of more than 80 agricultural productions such as cotton, maize, rice, sorghum, alfalfa, soybean and vegetables, all over Africa, the Mediterranean Basin and the Middle East (Salama et al, 1971). Its sex pheromone blend, variable according to the strains and areas, is composed of up to eleven 14-carbon acetates, among which (Z,E)-9,11-14:OAc is always the major component (Muñoz et al, 2008;Saveer et al, 2014). Electrophysiology experiments on male antennae identified one OSN population specifically tuned to this component (Ljungberg et al, 1993;Quero et al, 1996) and housed in one class of long trichoid sensilla, further referred as LT1 sensilla.…”
Section: Introductionmentioning
confidence: 99%
“…It is a serious pest of more than 80 agricultural productions such as cotton, maize, rice, sorghum, alfalfa, soybean and vegetables, all over Africa, the Mediterranean Basin and the Middle East (Salama et al, 1971). Its sex pheromone blend, variable according to the strains and areas, is composed of up to eleven 14-carbon acetates, among which (Z,E)-9,11-14:OAc is always the major component (Muñoz et al, 2008;Saveer et al, 2014). Electrophysiology experiments on male antennae identified one OSN population specifically tuned to this component (Ljungberg et al, 1993;Quero et al, 1996) and housed in one class of long trichoid sensilla, further referred as LT1 sensilla.…”
Section: Introductionmentioning
confidence: 99%
“…The antennae did not show a clear response to the other acetates present in female gland extracts. The biosynthetic route of the pheromone components in moths shows that 16:OAc and Z11-16:OAc are the precursors of Z9-14:OAc, Z7-12:OAc and Z9,E12-14:OAc (Jurenka, 2004;Groot et al, 2008;Saveer et al, 2014), therefore, these compounds are not directly involved in male attraction. Batista-Pereira et al (2006) reported that Z11-16:OAc did not increase male attraction to a synthetic blend of S. frugiperda pheromone containing Z7-12:OAc and Z9-14:OAc.…”
Section: Resultsmentioning
confidence: 99%
“…Pheromone glands were extracted in redistilled heptane (Labscan, 20 ml/10 glands) as previously described [18]. A subsample of extracts was used for chemical analysis.…”
Section: (D) Female Pheromone Gland Extraction and Chemical Analysismentioning
confidence: 99%
“…The initial temperature of the GC was set to 808C (5 min hold) and then increased 108C min 21 to a final temperature of 2258C (10 min hold). Pheromone components were identified by co-injection of authentic synthetic samples and comparison with a NIST mass spectra library (Agilent) and our own library [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation